IMPACT OF AIR POLLUTION ON SERUM AND SALIVA NITRIC OXIDE, PEROXY NITRITE AND ISCHEMIA MODIFIED ALBUMIN IN THE WORKERS EXPOSED TO HEAVY FUEL OIL COMBUSTION’S FUMES: IMPACT OF AIR POLLUTION ON SERUM AND SALIVA NITRIC OXIDE, PEROXY NITRITE AND ISCHEMIA MODIFIED ALBUMIN IN THE WORKERS EXPOSED TO HEAVY FUEL OIL COMBUSTION’S FUMES (Iraqi Journal of Market Research and Consumer Protection, 2024)
The object of this study was to measure the effect of air pollution on the health of the workers exposed to the heavy fuel oil (HFO) combustion fumes. This was achieved by testing the alteration in the levels of saliva and serum nitric oxide (NO), peroxynitrite (ONOO¯) and ischemia modified albumin (IMA). The participants enrolled in this study were male workers (N= 59) at heavy fuel oil combustion unit in Dora station of electricity in Iraq. Healthy individuals with matched age and body mass index (N=53) were also enrolled in the study to be used as a control group. The results detected a significant increase in the level of serum nitric oxide (NO) and peroxy nitrite (ONOO¯) (p0.005) of the workers group when compared with that of control group. The measured parameters also included measurement of serum and salivary level of ischemic modified albumin (IMA), which showed a highly significant increases (p